2018
DOI: 10.1038/s41416-018-0267-7
|View full text |Cite
|
Sign up to set email alerts
|

Statins attenuate outgrowth of breast cancer metastases

Abstract: BackgroundMetastasis in breast cancer foreshadows mortality, as clinically evident disease is aggressive and generally chemoresistant. Disseminated breast cancer cells often enter a period of dormancy for years to decades before they emerge as detectable cancers. Harboring of these dormant cells is not individually predictable, and available information suggests that these micrometastatic foci cannot be effectively targeted by existing therapies. As such, long-term, relatively non-toxic interventions that prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 52 publications
(81 reference statements)
7
68
0
Order By: Relevance
“…In vivo, in two independent models of breast cancer metastasis to liver and to lung, atorvastatin reduced proliferation of the metastatic, but not the primary, tumour cells. 66 Interestingly, in a large panel of cancer cell lines of multiple cancer types, it was shown that enrichment of EMT features in cells is associated with increased sensitivity to statins, which is independent from prenylation of RAS family proteins. 67…”
Section: Effect Of Statins On Epithelialmesenchymal Transition Of Cellsmentioning
confidence: 99%
“…In vivo, in two independent models of breast cancer metastasis to liver and to lung, atorvastatin reduced proliferation of the metastatic, but not the primary, tumour cells. 66 Interestingly, in a large panel of cancer cell lines of multiple cancer types, it was shown that enrichment of EMT features in cells is associated with increased sensitivity to statins, which is independent from prenylation of RAS family proteins. 67…”
Section: Effect Of Statins On Epithelialmesenchymal Transition Of Cellsmentioning
confidence: 99%
“…Recently, both preclinical and clinical studies have demonstrated beneficial effects of statins on breast cancer management ( Van Wyhe et al, 2017 ; Beckwitt et al, 2018a ; Li et al, 2019 ). Indeed, several in vitro and animal experiments have shown that statins exert positive anti-tumor effects by increasing breast cancer apoptosis ( Åberg et al, 2008 ; Kamel et al, 2017 ), preventing carcinogenesis ( Denoyelle et al, 2001 ), and inhibiting tumor growth ( Wolfe et al, 2015 ; Beckwitt et al, 2018b ). It should be noted that while most clinical studies showed positive effects of statins in management of breast cancer patients, while some clinical studies showed no or even opposite results ( Borgquist et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, statins have also received attention regarding unpredictable benefits to reduce breast cancer progression and mortality ( Liu et al, 2015 ; Borgquist et al, 2018 ; Gobel et al, 2019 ) and restrain breast cancer cell migration ( Ginestier et al, 2012 ; Van Wyhe et al, 2017 ; Gobel et al, 2019 ). Particularly, simvastatin, as one of the most commonly used statins, has demonstrated significant beneficial effects in reducing breast cancer metastasis and recurrence ( Ahern et al, 2011 ; Chae et al, 2011 ; Clendening and Penn, 2012 ; Beckwitt et al, 2018b ; Li et al, 2019 ). However, the underlying mechanisms by which statins inhibit tumor cell metastasis are not fully understood, although several studies have implicated the Rho/ROCK pathway, which is inhibited by statin treatment, as a key mechanism involved in regulation of cancer survival, proliferation, and invasion by statins ( Denoyelle et al, 2001 ; Demierre et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, simvastatin treatment reduced the activity of Rho associated protein kinase (ROCK) and expression of RhoC, chemokine receptor type 4 (CXCR4), and CD44 [ 94 ]. In a sophisticated ex vivo microphysiological model of breast cancer metastasis to the liver, breast cancer outgrowth in response to an inflammatory lipopolysaccharide/EGF stimulus could be suppressed with atorvastatin treatment [ 95 ]. Finally, we have shown in mouse models of spontaneous breast cancer metastasis to liver and lung that atorvastatin is able to suppress metastatic proliferation but not the proliferation of the primary tumor [ 95 ].…”
Section: Basic Research Studiesmentioning
confidence: 99%
“…In a sophisticated ex vivo microphysiological model of breast cancer metastasis to the liver, breast cancer outgrowth in response to an inflammatory lipopolysaccharide/EGF stimulus could be suppressed with atorvastatin treatment [ 95 ]. Finally, we have shown in mouse models of spontaneous breast cancer metastasis to liver and lung that atorvastatin is able to suppress metastatic proliferation but not the proliferation of the primary tumor [ 95 ]. These data suggest that statins preferentially target mesenchymal, metastatic cells.…”
Section: Basic Research Studiesmentioning
confidence: 99%